2014 IEEE Computer Society Annual Symposium on VLSI 2014
DOI: 10.1109/isvlsi.2014.33
|View full text |Cite
|
Sign up to set email alerts
|

SET Susceptibility Analysis of Clock Tree and Clock Mesh Topologies

Abstract: Clock distribution networks represent one of the most important signals in a synchronous integrated circuit, this signal may be altered by radiation effects and generate an abnormal behavior in the system. In this work we analyzed two types of clock distribution network using the same circuit to know which of one is more sensitive to radiation threats. Using a case study we compare clock tree with clock mesh. Finally we found that clock mesh topology is more sensitive to radiation effects in comparison with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Chipana et al [14] analyzed the two types of CDN to investigate the sensitivity to the radiation threats. The comparison between the clock mesh and clock tree showed that the clock mesh has the higher sensitivity to the radiation threats.…”
Section: Related Workmentioning
confidence: 99%
“…Chipana et al [14] analyzed the two types of CDN to investigate the sensitivity to the radiation threats. The comparison between the clock mesh and clock tree showed that the clock mesh has the higher sensitivity to the radiation threats.…”
Section: Related Workmentioning
confidence: 99%
“…In the deep submicron regime, CDNs contribute significantly to the chip-level soft error rate (SER) [2] and radiation particle strikes on the CDN can prove to be catastrophic [3]. Abnormal behaviors in the whole system may be generated if the clock signal is altered by radiation effects [4,5]. To mitigate and avoid mistaken data latching or failure of the whole circuit system caused by SETs on the clock signal, efficient hardening techniques for the CDN should be proposed.…”
mentioning
confidence: 99%